Functional disability and morbidities among the elderly people, according to socio-demographic conditions and indicative of depression - Bárbara Ferreira Agreli (Universidad de Antioquia, 2017)
Objectives. To investigate the association of functional incapacity and the number of morbidities with sociodemographic, economic and health variables.